LINGUISTIC FEATURES OF THE MODERN NEWSPAPER LANGUAGE: ANALYSIS AND RESEARCH - Bobojonov, Dilshod; Halilova, Shohista; Umarova, Maftunbonu; Turdaliyeva, Shahnoza; Xolmurodova, Gulnora (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
In contemporary high-choice media environments, the issue of media trust and its impact on people's media use has taken on new importance. At the same time, the extent to which people trust the news media and how much it matters for their use of different types of media is not clear. To lay the groundwork for future research, in this article we offer a focused review of how news media trust has been conceptualized and operationalized in previous research and research on the extent to which news media trust influences media use, and offer a theoretically derived framework for future research on news media trust and its influence on media use.